94.8k views
5 votes
Find the integral, using techniques from this or the previous chapter.
∫xex dx.

User Cuuupid
by
5.8k points

1 Answer

4 votes

Answer:


xe^(x) - e^(x) +C

Explanation:

we will solve this using integration by parts as the problem is a product of two functions which none of them are constants.

∫udv = uv -∫vdu ..............equ 1


xe^(x)

u=x ,

du= 1

dv =
e^(x)

v=∫dv=
e^(x)

Substituting into equ 1

∫udv =
xe^(x) - ∫
e^(x)dx

∫udv =
xe^(x)- e^(x) + C

User RWIL
by
6.0k points